Questioning the Difference between Socrates and Sophists: Philosophical Dialogue with Regard to Facticity and Power - Gutauskas, Mintautas (Problemos, 2007)
The question raised in the article is why do postmodern thinkers reduce philosophical cognitive dialogue to struggle of powers or the play of effects, thereby eliminating philosophically significant difference between Socrates and a sophist. While upholding the view that sustaining this difference is still significant for philosophy, the author attempts to critically assess the consequences abandoning this difference would have for the philosophical dialogue and seek the arguments for justifying this difference. The classical Platonic dialogue always contains an hierarchizing dimension – the logos of the dialogue, which allows to evaluate the factual weight and cognitive value of every opinion. This logos as the common reason, rules and measure has been the principle of the dialogue enabling the discovery of common truth. Once F. Nietzsche has revealed the pursuit of truth as a manifestation of the will to power, one has the possibility to reduce philosophical dialogue to the struggle of the wills to power. And once G. Deleuze has revealed simulacric character of phenomena, one has the possibility to reduce philosophical dialogue to the play of simulation effects. The will to power and simulation appear as a deeper realm governing the dialogue. But does philosophical dialogue remain philosophical? Postmodernists tend to totalize interpretation and simulation. One must return to the question of givenness of matter of fact. The fact that experience is given only interpretations, does not mean that interpretations can abandon facticity. According to H. G. Gadamer and G. Figal one can distinguish between assimilation and interpretation. The principle of the former is the will, and it is conquering and ruling of the world. The latter, though similar to assimilation, preserves the distance and the difference with regard to matters of fact, and in virtue of its critical reflection it is capable of keeping its referential function. And even though critical reflection cannot be the ultimate and absolute instance, it is nevertheless capable of distinguishing between deceptive evidence (effect) from reliable evidence (“things themselves”).
Keywords: Socrates, sophists, Nietzsche, Deleuze, philosophical dialogue, power